(untitled) (Raparin Journal of Humanities (RJH), 2025)
This research aims at presenting the opinions of the four ancient schools of thought، the contemporary scholars، and the Iraqi law about the inclusion of medical expenses in the spousal alimony. It also analyzes the arguments and proofs each group presents in regard to this subject in accordance with the status quo. Research methods This research uses both descriptive and analytical methods by explaining the points of views of the scholars and then analyzing them through the lenses of the books and scholarly opinions. Research conclusions The scholars of all four schools of thought have concluded that medical expenses are not considered a part of spousal alimony. They have based their judgment on (customs). In the ancient times، medical expenses were not among the basic needs of humans، because most of the medicines were home and locally made، and therefore were not of considerable cost. Also، there were no specialized medical institutions. Nowadays، however، things have changed. Therefore، modern scholars and the Iraqi law have ruled to include such expenses in the spousal alimony. Ideas and judgments change based on different circumstances، times and even persons، as such، this is the prevailing opinion of this era. Authenticity of search This research addresses a current and a real issue in the subject of spousal alimony and whether it covers medical expenses. It presents the case depending on the theories and ideas of various old and modern scholars and the Iraqi law.